Wound Healing in a Patient with Psoriasis Vulgaris and Femur Megaprosthesis Implantation - Nottrott, Markus (Hindawi Publishing Corporation, 2008)
Extraskeletal mesenchymal chondrosarcoma is extremely rare and, in combination with psoriasis, it has never been described before. We report a case of wide resection of an extraskeletal chondrosarcoma of the thigh and reconstruction with a femoral megaprosthesis in a patient with psoriasis vulgaris. Special emphasis has been laid to postoperative wound healing in psoriatic skin which did not show any problems.